Uterine prolapse and pregnancy. - Alegría, Raúl (2015)
OBJECTIVE: To present a case of uterine prolapse and pregnancy attended at "Guillermo Almenara Irigoyen", Hospital and determine risk factors for presentation. DESIGN: Descriptive clinical case study. RESULTS: We identify the risk factors for genital prolapse in our population. CONCLUSIONS: Uterine prolapse during pregnancy is not frequent. Adequate knowledge of its causes, complications and postpartum management will lead us to adequate preventive measures.